(untitled) (International journal of artificial intelligence, 2026)
This article covers the lexical and historical definition of the concept of enlightenment, as well as the views of the independence period, the formation of the educational system, its role in pedagogical processes, goals and objectives, categories, and the need for enlightenment in each period.